Geodiversity and abiotic ecosystem services in parks from the far north of Minas Gerais: educational and geotourism potential - Pressi, Leonardo Frederico; Castro, Paulo de Tarso Amorim (Revista Cerrados, 2023)
The state parks from the far north of Minas Gerais are strategic for raising society's awareness about the importance of nature. Considering that in the State Parks of Montezuma, Caminho dos Gerais (PECGerais), and Serra Nova e Talhado (PESNT), there are important abiotic ecosystem services, geodiversity must be incorporated into environmental interpretation activities. In this work, sites intended for public use were evaluated regarding their educational and touristic potential related to geodiversity and the degradation risk. Geosites and geodiversity sites were selected in which geological processes can be approached by weaving relationships with biodiversity and cultural aspects to encourage visitors to have a holistic view of nature. These sites also encourage discussion on various Sustainable Development Goals – SDGs. Considering that they are located in a region with a semi-arid climate and that these parks are essential for the water supply in their surroundings, aspects related to water resources are of great relevance and may unequivocally be addressed in all selected sites, especially in the Talhado Canyon (PESNT), Gameleiras Dam (PECGerais) and in the Lagarto Rock (PEM). The intrinsic relationship between geodiversity and biodiversity is observed at the Peatlands of Gerais Santana (PESNT), Vereda das Piranhas Trail (PECGerais) and the Lavra Trail (PEM) sites. The relationship between geodiversity and cultural aspects of the region are evident in all selected sites. The high educational and geotourism potential, associated with the low degradation risk, indicates that all these sites are useful for public use activities.